2004
DOI: 10.1021/bm0343904
|View full text |Cite
|
Sign up to set email alerts
|

NMR Characterization of Native Liquid Spider Dragline Silk fromNephila edulis

Abstract: Solid spider dragline silk is well-known for its mechanical properties. Nonetheless a detailed picture of the spinning process is lacking. Here we report NMR studies on the liquid silk within the wide sac of the major ampullate (m.a.) gland from the spider Nephila edulis. The resolution in the NMR spectra is shown to be significantly improved by the application of magic-angle spinning (MAS). From the narrow width of the resonance lines and the chemical shifts observed, it is concluded that the silk protein wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
76
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(85 citation statements)
references
References 39 publications
7
76
0
Order By: Relevance
“…[73][74][75][76] The spectrum is also comparable to that obtained for the in vitro dissolution of recombinant MaSp1 and MaSp2 proteins. The conformation of the spinning dope that has flowed out of the gland is basically identical to the native silk contained in the sac of the gland, and is slightly affected by dehydration.…”
Section: Structure Of Silk By Raman Spectromicroscopysupporting
confidence: 66%
“…[73][74][75][76] The spectrum is also comparable to that obtained for the in vitro dissolution of recombinant MaSp1 and MaSp2 proteins. The conformation of the spinning dope that has flowed out of the gland is basically identical to the native silk contained in the sac of the gland, and is slightly affected by dehydration.…”
Section: Structure Of Silk By Raman Spectromicroscopysupporting
confidence: 66%
“…secondary structures despite their different amino acid sequences. Major ampullate spidroins (MaSps) are known to be mostly unfolded in the gland, 24,25 but vibrational circular dichroism and NMR spectroscopies have clearly shown that they contain a significant amount of left-handed 3 1 -helices [also known as polyproline II (PPII) helices], which have been suggested to be important for the formation of β-sheets during the spinning process. 23 From the similarity of the Raman spectra of the Ma and Mi silks, it can be hypothesized that the Mi proteins also contain a significant amount of PPII helices.…”
Section: Resultsmentioning
confidence: 99%
“…[9] Furthermore, assemblies of chitin and silk in vitro do not provide either images or diffraction patterns any different from chitin alone, again implying that the silk fraction is not ordered. [18] Spider silk only becomes fibrillar and ordered during its extrusion from the silk gland. [17] It is thus relevant to note that spider silk in the silk gland is highly concentrated, hydrated, and not ordered.…”
Section: Discussionmentioning
confidence: 99%